دراسة مناعية لمجموعة من مدخنين السكائر (نساء ورجال) في مدينة بغداد - عليوي سناء رحمن (Al-Nahrain Journal of Science, 2009)
The aim of study is found the effect of cigarette smoking on some immunological parameters which include immunoglobulins, complement proteins 3, 4 (C3, C4), acute phase proteins is ceruloplasmin and white blood cell count (WBC). There is significant decrease in immunoglobulin G(IgG) level in smokers (women, men) as compared with control but this decrease in women was greater. There is significant increase in level of IgM in all smokers but was more increased in men smokers as compared with control while there is significant decrease in IgA level in women smokers and non significant in men smokers. There is significant increase in C3 level in all smokers compared with control especially for women, while level of C¬4 was showed no significant increase. The results of the effect of smoking on ceruloplasmin protein level in serum showed that there is significant increase in women smokers. Also there is significant increase in WBC count generally in all smokers but in men more than in women.The conclusion of this study is that cigarette smoking have important role in occurrences of alternation or dipression in immune system and showed increase of risk of cardiovascular diseases was showed greater effect in women than in men.